Reactor and process for the production of sodium zirconium cyclosilicate
Patent Information
- Application Number
- CN202510796260.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-13
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-06-13
AI Technical Summary
说明该专利实施例3制备的所谓的ZS-9并没有达到环硅酸锆钠的硅含量,杂质过多或者有其他晶型,不符合用药要求
[0051]1.本发明提供的设备在单位体积下与现有技术水平相比,明显提高了产能,从而满足对药品的可获得性且降低了产品的经济成本。
Smart Images

Figure CN120984211B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the fields of improving pharmaceutical production capacity and impurity control, and in particular to reactors and methods for producing sodium zirconium cyclosilicate, as well as sodium zirconium cyclosilicate with controlled elemental impurity content. Background Technology
[0002] Hyperkalemia is a critical metabolic disorder that commonly occurs in patients with chronic kidney disease, heart failure, diabetes, and hypertension. According to epidemiological data in my country, the prevalence of chronic kidney disease (CKD) is approximately 10.8%, affecting about 120 million people, of whom about 1.92 million have end-stage renal disease (ESRD). Hyperkalemia is relatively common among CKD patients, suggesting that there are at least 2 million hyperkalemia patients in my country.
[0003] Sodium zirconium cyclosilicate powder is a medication for treating hyperkalemia and has been included in the second batch of the "List of New Drugs Urgently Needed in Clinical Practice from Overseas". The drug's instructions state that its active ingredient's chemical name is sodium zirconium silicate hydrate, with the molecular formula Na. ~1.5 H ~ 0.5 ZrSi3O9·2-3H2O (hereinafter referred to as sodium zirconium cyclosilicate) is indicated for the treatment of hyperkalemia in adults. This product is a white to gray powder. The recommended starting dose is 10 g, three times daily for a maximum of 48 hours, administered orally. For the maintenance phase, the recommended starting dose is 5 g once daily. Therefore, the future demand for sodium zirconium cyclosilicate powder for the treatment of hyperkalemia is extremely large, with calculated daily consumption exceeding 60 tons. How to stably produce this drug in large quantities is a technical problem that needs to be solved.
[0004] The contents of sodium zirconium cyclosilicate powder are sodium zirconium cyclosilicate raw materials, without excipients. The main (over 95%) crystal form is ZS-9. Other crystal forms have weak potassium ion adsorption capacity, reducing efficacy. According to the preparation method reported in US Patent 5891417 published in 1999, it is prepared by a hydrothermal reaction of sodium silicate, sodium hydroxide, and zirconium acetate in an aqueous medium. The X-ray diffraction parameters of ZS-9 are shown below. The designation "ZS-9" indicates that this crystal form is well known in the art.
[0005]
[0006]
[0007] The American Chemical Society publication *Organic Process Research & Development*, 2024, 28, 5, 1929-1937, reports that the synthesis mechanism of sodium zirconium cyclosilicate involves the following process:
[0008] 3(Na₂O·SiO₂)(aq)+[ZrO₃] 2- +2.7H2O+4HOAc
[0009] →Na2ZrSi3O9·2.7H2O+4NaOAc+2OH - +H2O
[0010] Based on the principle of hydrothermal reaction, the sodium hydroxide solution reacts with sodium silicate, breaking the covalent bonds between silicon and oxygen in the sodium silicate and degrading it into an oxysilicate polymer. Meanwhile, the zirconium acetate composite polymer precipitates as hydrated zirconium oxide upon contact with an alkaline medium. The two form a slurry, which is then dehydrated under high temperature and pressure to form sodium cyclosilicate.
[0011] Chinese invention patent CN103534209A was the first to disclose equipment and methods for large-scale preparation of sodium zirconium cyclosilicate (ZS-9) crystals. Example 15 disclosed a reactor for large-scale preparation of high-purity, high-KEC (ion exchange coefficient) ZS-9 crystals, specifically by adding baffles around the reactor. Patent CN104797263B disclosed the preparation of sodium zirconium cyclosilicate using a 200L reactor, but did not disclose the reactor material. The material usage was: 56.15 kg sodium silicate, 101.18 kg deionized water, 7.36 kg sodium hydroxide, and 23 kg zirconium acetate, totaling 187.69 kg. The patentee claimed that the material filled 80-90% of the reactor volume. However, the yields of four batches were 16.60 kg, 16.65 kg, 16.61 kg, and 16.14 kg, respectively. That is, the material ratio (product weight kg / reactor volume L) that can be produced at a scale of 200L is approximately 8.25%, and a considerable portion of the sodium zirconium cyclosilicate prepared by this patent is ZS-7, approximately 28%. ZS-7 and ZS-9 cannot be separated by known methods. ZS-7 has poor potassium ion exchange capacity. The product prepared by CN104797263B does not meet the requirements for pharmaceutical use and cannot be compensated for by purification methods. This method has no practical value in pharmaceutical production.
[0012] Besides production volume issues, the safety concerns arising from metal residues also warrant attention. Given the large daily dosage of this drug and the patient's impaired kidney function and poor excretion, the presence of metallic impurities in the product, particularly lead and nickel, must be strictly controlled to prevent further kidney damage.
[0013] Based on the product characteristics and the ICH Q3D guidelines for controlling elemental impurities in pharmaceuticals, sodium zirconium cyclosilicate ZS-9 is an inorganic compound. To ensure medication safety, it is necessary to strictly control any potential elemental impurities. The ICH Q3D Guideline for Elemental Impurities specifies that for Class 1 impurities, the permissible daily exposure (PDE) for lead in oral formulations is 5 μg / day, calculated as concentration (μg / g) = PDE (μg / day) / daily dose (g / day). Given the recommended dose of sodium zirconium cyclosilicate powder is 10g three times daily (30g daily), the lead level must be below 0.17 ppm. For Class 2A impurities, the permissible daily exposure (PDE) for nickel in oral formulations is 200 μg / day, requiring a nickel level below 6.67 ppm. Since patients may ingest metal elements through other routes and often have poor renal function, lower levels of metal impurities in the drug generally indicate better safety.
[0014] Sodium zirconium cyclosilicate is insoluble in water and organic reagents. Once crystallization is complete, the finished product is obtained. If other impurities enter the product during the crystallization stage, they cannot be removed in subsequent processing. Therefore, in addition to controlling heavy metal residues in the raw materials, precise control must be exercised during the hydrothermal reaction process to prevent metal impurities from entering the product.
[0015] Patent CN108137620B claims that lead impurities need to be controlled, and abandons commercially available sodium silicate with high lead content, replacing it with colloidal silica with lower lead content. Although it claims that the lead content is preferably controlled at 0.1 ppm, this was not actually achieved in the examples. In its optimal example 3, colloidal silica was used as the starting material to prepare sodium zirconium cyclosilicate ZS-9, and the lead content of the sodium zirconium cyclosilicate ZS-9 prepared in this example reached 0.38 ppm. This exceeds the recommended elemental impurity control requirement (0.17 ppm) for sodium zirconium cyclosilicate powder at the recommended dosage. Furthermore, both Examples 2 and 3 were prepared on a scale of 500L for ZS-9. The elemental impurities nickel and molybdenum were detected. For the recommended dosage of 10g three times daily, the limit for nickel, according to the calculation formula, should be below 6.7 ppm. Examples 2 and 3 showed levels of 2.79 and 2.56 ppm respectively, which, while meeting the limit, are still relatively high. Nickel was not detected in the raw materials sodium silicate, zirconium acetate, and colloidal silica used in Examples 2 and 3 for preparing zirconium silicate, but it was detected in the final product. In addition, the product obtained in Patent Example 3 contained approximately 21.7% zirconium, approximately 17% silicon, and approximately 7.3% sodium. According to the product instructions for sodium zirconium silicate powder, its molecular formula is Na. ~1.5 H ~0.5ZrSi3O9·2-3H2O has a molecular weight of 390.5–408.5 Daltons. Based on this molecular formula and molecular weight, the silicon content should be 20%–23%; the zirconium content should be 21%–24%; and the sodium content should be 7%–9%. This indicates that the so-called ZS-9 prepared in Example 3 of this patent does not meet the silicon content requirements of sodium zirconium cyclosilicate, has too many impurities or other crystal forms, and does not meet the requirements for pharmaceutical use.
[0016] In summary, the technical problems that urgently need to be solved in this field are: (1) how to increase the production capacity of qualified products in order to reduce production costs; and (2) how to reduce the content of elemental impurities in order to improve drug safety. Summary of the Invention
[0017] To address the above problems, this application proposes a reactor for producing sodium zirconium cyclosilicate.
[0018] The reactor has a main body 1 and a stirring device 2, and the main body 1 has a volume of 500L or more.
[0019] The inner wall 11 of the main body 1 is provided with at least two baffles 111.
[0020] The stirring device includes at least one set of blades 21, each set of blades 21 having at least two blades 21; the power unit 4, located above the outside of the main body 1, drives the blades 21 to stir via the stirring shaft 22.
[0021] A mechanical seal 3 is provided between the stirring device 2 and the main body 1.
[0022] The inner bottom 12 and inner sidewall 11 of the main body 1, at least one surface of the baffle 111, and the surface of the blade 21 are made of a wear-resistant material with a Brinell hardness greater than 200 HB.
[0023] Although this application only emphasizes wear resistance (hardness), those skilled in the art will readily understand that, since the production of sodium zirconium cyclosilicate requires a hydrothermal reaction under strongly alkaline conditions, the material must also be resistant to strong alkalis; otherwise, it would be impossible to use it to manufacture certain reactors.
[0024] The wear-resistant material has a Brinell hardness of 200 HB or higher, preferably 210 HB or higher, and more preferably 220 HB or higher. Preferably, the wear-resistant material is a Hastelloy alloy, more preferably an N10276 alloy (also known as a C276 alloy) or an N06022 alloy (also known as a C22 alloy).
[0025] Compared to 316L stainless steel (187HB Brinell hardness) commonly used in alkali-resistant equipment in the chemical industry, Hastelloy alloy, which has a higher Brinell hardness, has better wear resistance and can effectively prevent alloy debris from being mixed into the product.
[0026] The inner bottom 12 and inner sidewall 11 surfaces inside the main body 1, at least one surface of the baffle 111, and the surface of the blade 21 are made of wear-resistant material, which can be achieved in the following ways.
[0027] As one implementation method, Hastelloy can be used to manufacture the entire reactor body 1, impeller 21, and baffle 111. However, Hastelloy is expensive, resulting in high production costs.
[0028] As a preferred way to reduce costs, Hastelloy can be used only for the wear-prone parts that come into contact with the reaction liquid, such as the blade 21, one side of the baffle 111, and the inner bottom 12 and inner sidewall 11 inside the reactor 1, while other materials such as 316L stainless steel can be used for the outer shell that does not come into contact with the reaction liquid. The inner top 13 inside the reactor 1 is not easily corroded by particles, so Hastelloy may not be used, but a material resistant to alkaline corrosion, such as stainless steel, should still be used.
[0029] Those skilled in the art will readily understand that when the stirring is turned on, the side of the baffle 111 that is subjected to fluid impact should be fitted with a wear-resistant Hastelloy plate, while the other side can be made of stainless steel.
[0030] The Hastelloy plates can be installed using known fixing methods or metal processing methods, such as welding, bolting, explosive bonding, etc., with explosive bonding being the preferred method.
[0031] The reactor volume can be 500L, 750L, 800L, 1000L, 1200L, 1250L, 1500L, 1800L, 2000L, etc.
[0032] The reactor according to claim 1 is characterized in that the thickness of the wear-resistant material is greater than 3 mm. Considering the maintenance cycle and initial cost, this thickness can be set to, for example, 3 mm, 5 mm, 8 mm, 10 mm, 12 mm, etc.
[0033] As an example, the main body 1 is made of stainless steel, with wear-resistant material only provided on the inner bottom 12 and inner side 11; the baffle 111 and the blade 21 are made of Hastelloy as a whole.
[0034] Preferably, the ratio of the length of the impeller 21 to the radius of the cross-section of the reactor body 1 in the horizontal plane is 0.4 to 0.6:1. The length of the impeller 21 is defined as the horizontal distance from the axis of the stirring device to the farthest end of the impeller 21.
[0035] Preferably, the mechanical seal 3 is a double-end mechanical seal. Double-end mechanical seals are common parts in chemical equipment, and there are many commercially available products. This application will not provide their detailed mechanical structure.
[0036] Those skilled in the art will know that, as a chemical equipment, the main body 1 in actual use is also equipped with a feed inlet, a discharge outlet, a heating device, a temperature control device, a pressure detection device, an observation port, a fixed base, etc. The positions and dimensions of these are conventional designs in the chemical industry and do not involve the technical problem to be solved in this application, so this application will not elaborate further.
[0037] This application also proposes a method for preparing sodium zirconium cyclosilicate. In the reactor, a mixture of sodium hydroxide, colloidal silica, zirconium acetate, and water is prepared with a filling coefficient of 0.7–0.9. The mixture is then subjected to a hydrothermal reaction at 200–215°C and stirring at 80–120 rpm for 24–48 hours. The filling coefficient, also known as the loading coefficient, refers to the proportion of the total volume of the feed material to the reactor volume.
[0038] Preferably, the amount of zirconium acetate and colloidal silica in each liter of reaction solution is 0.18 kg to 0.2 kg.
[0039] This application also provides a sodium zirconium cyclosilicate raw material, wherein the sodium zirconium cyclosilicate has the molecular formula Na. ~1.5 H ~ 0.5 ZrSi3O9·2-3H2O; the ZS-9 crystal form accounts for more than 95% of the active pharmaceutical ingredient; the active pharmaceutical ingredient is a solid powder, and the lead content in the active pharmaceutical ingredient is <0.17ppm and the nickel content is ≤2.0ppm.
[0040] Preferably, the elemental content of the active pharmaceutical ingredient conforms to the following: silicon content: 21%–22%, zirconium content: 22%–23%, sodium content: 7%–9%, lead content <0.1ppm, cobalt content ≤1.0ppm, chromium content ≤5.0ppm, nickel content ≤1.0ppm, and molybdenum content ≤0.3ppm.
[0041] This application also provides a pharmaceutical composition containing the aforementioned sodium zirconium cyclosilicate active pharmaceutical ingredient. The pharmaceutical composition may contain only sodium zirconium cyclosilicate active pharmaceutical ingredient (e.g., AstraZeneca's sodium zirconium cyclosilicate powder), or it may be prepared into other dosage forms, such as suspensions, by adding suspending agents, flavoring agents, etc.
[0042] During their research on the production process, the inventors discovered that the lead content was relatively higher in products with smaller particle sizes, speculating that this might be due to the adsorption effect of small particles on lead ions. Therefore, the inventors used a slower stirring speed to prepare larger particles, ensuring that particles smaller than 3 micrometers did not exceed 1% of the total volume, successfully reducing the lead content of the product to below 0.17 ppm, while simultaneously maintaining a ZS-9 content exceeding 95%. When the product contained no particles smaller than 3 micrometers, the lead content was as low as 0.002 ppm, or undetectable.
[0043] To address the presence of trace amounts of nickel and other components in existing technologies, the inventors conducted multiple experiments using a 316L stainless steel reactor (US standard 316L, corresponding to grade 022Cr17Ni12Mo2 in Chinese standard GB / T20878-2024) commonly used in alkali-resistant equipment in the chemical industry. They discovered that in addition to the nickel impurity disclosed in existing technologies, iron, chromium, molybdenum, and cobalt impurities were also detected, closely resembling the composition of stainless steel. Furthermore, the longer the single reaction time, the larger the particles, and the older the equipment, the higher the impurity content. During reactor maintenance, scratches were found inside the reactor. Based on this, the inventors hypothesize that the impurities originate from the continuous friction between the product particles and the stainless steel surface within the reactor during high temperature and high pressure due to the large quantity and coarse particle size, causing stainless steel debris to detach and enter the product.
[0044] The Brinell hardness of 316L stainless steel is less than 187 HB. When reactors, baffles, and impellers are made of Hastelloy alloy with a Brinell hardness exceeding 200 HB, the content of impurities such as nickel is significantly reduced, and other impurities do not exceed the standard. This proves that using high-hardness wear-resistant materials helps reduce elemental impurities. Pure Hastelloy reactors are too expensive and difficult to process. Therefore, a Hastelloy alloy lining can be used, where the inner bottom 12 and inner sidewall 11 surfaces of the main body 1, at least one surface of the baffle 111, and the impeller 21 are made of wear-resistant material with a Brinell hardness greater than 200 HB. This achieves the same technical effect and facilitates maintenance and replacement.
[0045] The inventors also optimized the reactor sealing method. In existing technologies, magnetic sealing is generally used for pressurized reactions. The inventors discovered that when the reactor loading coefficient was filled to 0.4, the product output was normal. However, as the loading coefficient was increased, black spots gradually began to appear. When the coefficient was increased to above 0.8, a large number of black spots appeared in the prepared sodium zirconium cyclosilicate. Therefore, it can be concluded that when using magnetic sealing as the reactor sealing device, increasing the loading coefficient results in substandard material appearance in the product, affecting production efficiency.
[0046] After inspecting the equipment, it was found that when the filling ratio was high, the alkaline solution in the material entered the magnetic seal, causing the magnetic seal to corrode and black spots to fall into the product.
[0047] After replacing the reactor seal with a double-end mechanical seal, and using a reactor with a capacity of 1000L or more, the inventors added colloidal silica to a solution of sodium hydroxide and water, and then added zirconium acetate solution. When the filling ratio was the same at 0.8, they were surprised to find that there were no black spots in the 100kg of product produced, and no increase in elemental impurities was detected.
[0048] Therefore, when using mechanical seals, a higher filling factor can be adopted, thereby increasing output and reducing energy consumption.
[0049] Regarding the impeller length, the optimal operating condition of the equipment is achieved when the ratio of the reactor impeller length 21 to the inner cross-sectional radius of the reactor body is optimized to 0.4–0.6. If the impeller is too short, the stirring efficiency is poor; if the impeller is too long, the energy consumption is high.
[0050] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0051] 1. The equipment provided by this invention significantly improves production capacity per unit volume compared with the prior art, thereby satisfying the demand for drug availability and reducing the economic cost of the product.
[0052] On the one hand, the equipment has a high filling coefficient, and even with large amounts of material fed in, impurities will not be generated due to corrosion of the magnetic seal. The amount of sodium zirconium cyclosilicate produced per unit volume is 10% to 12.5% (equivalent to 100-125 kg of product per batch from a 1000 L reactor). On the other hand, the equipment is equipped with a wear-resistant layer, eliminating the need for frequent maintenance. In a preferred embodiment, the wear-resistant layer can be a fixed Hastelloy plate, which is easy to replace.
[0053] 2. The method provided by this invention reduces the stirring speed, thereby obtaining larger particles and a high ZS-9 content.
[0054] 3. The sodium zirconium cyclosilicate product produced by the new preparation method and equipment provided by this invention has a further reduced lead and nickel content compared with the prior art, and the content of other metal element impurities is extremely low or undetectable, thus ensuring drug safety. Attached Figure Description
[0055] Other features, objects, and advantages of this application will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings:
[0056] Figure 1 This is a schematic diagram of the crystal structure of sodium zirconium cyclosilicate ZS-9;
[0057] Figure 2 This is a schematic diagram of the vertical structure of the reactor;
[0058] Figure 3 This is a schematic diagram of the horizontal cross-section of the reactor;
[0059] Figure 4 This is a particle size distribution diagram of the product in Example 2.
[0060] In the picture:
[0061] 1. Main body; 2. Stirring device; 3. Mechanical seal; 4. Power unit; 11. Inner wall; 12. Inner bottom; 13. Inner top; 21. Blade; 22. Stirring shaft; 111. Baffle. Detailed Implementation
[0062] To better understand this application, the technical solutions of this application will be described in more detail with reference to the accompanying drawings. It should be understood that these detailed descriptions are merely illustrative of exemplary embodiments of this application and are not intended to limit the scope of this application in any way. Throughout the specification, the same reference numerals refer to the same elements. The expression "and / or" includes any combination or all combinations of one or more of the associated listed items.
[0063] In the accompanying drawings, the dimensions, scale, and shape of the illustrations have been slightly adjusted for ease of explanation. The drawings are for illustrative purposes only and are not drawn to scale. As used herein, the terms “approximately,” “about,” and similar terms are used as expressions of approximation, not as expressions of degree, and are intended to illustrate inherent deviations in measurements or calculations that will be recognized by one of ordinary skill in the art.
[0064] It should also be understood that expressions such as "comprising," "including," "having," "containing," and / or "comprising" are open-ended rather than closed-ended expressions in this specification, indicating the presence of the stated features, elements, and / or components, but not excluding the presence of one or more other features, elements, components, and / or combinations thereof. Furthermore, when expressions such as "at least one of..." appear after a list of listed features, they modify the entire list of features, not just a single feature in the list. Additionally, when describing embodiments of this application, the word "may" is used to mean "one or more embodiments of this application." And the term "exemplary" is intended to refer to examples or illustrations.
[0065] Unless otherwise specified, all terms used herein (including engineering and technical terms) shall have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. It should also be understood that, unless expressly stated herein, terms defined in common dictionaries shall be interpreted as having the meaning consistent with their meaning in the context of the relevant art, and not as having an idealized or overly formalized meaning.
[0066] It should be noted that, unless otherwise specified, the embodiments and features in the examples of this application can be combined with each other. Furthermore, unless explicitly limited or contradicted by the context, the specific steps included in the methods described in this application are not limited to the order in which they are described, but can be performed in any order or in parallel. This application will now be described in detail with reference to the accompanying drawings and embodiments.
[0067] The particle size testing method in this application is as follows: referring to the particle size detection method in the imported registration standard for sodium zirconium cyclosilicate powder. According to the Chinese Pharmacopoeia 2015 edition, Part IV, General Chapter 0982, Method III, water is used as the dispersion medium, and a wet method (such as a Malvern 3000 or other equivalent laser particle size analyzer) is employed for determination.
[0068] Methods for determining elemental impurities: Sodium zirconium cyclosilicate is an inorganic substance that is insoluble in water and is not absorbed in the body. Therefore, simulating human gastric and intestinal fluids, a leaching method was used to determine its metal element content. The determination method followed the inductively coupled plasma mass spectrometry method in General Chapter 0412 of the 2020 edition of the Chinese Pharmacopoeia, Part IV.
[0069] The elemental contents of Si, Na and Zr were determined using WD-XRF (wavelength dispersive X-ray fluorescence spectrometer).
[0070] The determination method for KEC refers to the method for detecting potassium ion exchange capacity in the import registration standard for sodium zirconium cyclosilicate.
[0071] Example 1
[0072] See Figure 2 and Figure 3 This describes the structure of the reactor.
[0073] 1 represents the main body of the reactor.
[0074] like Figure 3 As shown, for ease of stirring, the horizontal cross-section inside the reactor body 1 is circular, and its internal space can be capsule-shaped (see...). Figure 2 Alternatively, it can be changed to a cylindrical, spherical, or ellipsoidal shape.
[0075] In the main body 1, 11 is the inner sidewall, 12 is the inner bottom, and 13 is the inner top.
[0076] The inner bottom 12 can be flat. Considering the convenience of material discharge, the inner bottom 12 can be set as a downward convex arc surface, so that the internal space of the reactor body 1 is capsule-shaped or semi-capsule-shaped.
[0077] The inner sidewall 11 is provided with 2-6 vertical baffles 111. Figure 3 An example with four baffles 111 is shown, the baffles 111 being made of Hastelloy.
[0078] 2 is a stirring device, including a stirring shaft 22 and a blade 21 mounted on the stirring shaft 22; a power unit 4 is located above the reactor body 1 and is used to drive the stirring device 2; a mechanical seal 3 is provided between the stirring device 2 and the body 1.
[0079] Depending on the shape and size of the reactor, the stirring device 2 includes 1-5 sets of blades 21, with 2-6 blades in each set. Figure 2 and Figure 3 The illustration shows a configuration with 3 groups, each group consisting of 3 blades 21; the blades 21 are made of Hastelloy; a "group" of blades refers to multiple blades on essentially the same horizontal plane.
[0080] The length of the blade 21 is defined as the horizontal distance from the center of the stirring shaft 22 to the outermost end of the blade 21; in this embodiment, it is set to 0.5 times the inner radius of the reactor 1 on the horizontal plane where the blade 21 is located, and the blade 21 forms an angle of 30°-60° with the horizontal plane.
[0081] In this embodiment, Hastelloy is used to make the entire reactor body 1, baffle 111, and impeller 21 of the stirring device.
[0082] Example 2
[0083] The C276 reactor shown in Example 1 was used, with a volume of 1000L and the ratio of impeller length to reactor inner radius set to 0.4:1.
[0084] Sodium hydroxide (90 kg) and water (280 kg) were mixed and cooled to room temperature. Colloidal silica (240 kg) was added, and the mixture was stirred at 120 rpm. While maintaining this stirring speed, zirconium acetate (170 kg) was added. After the addition was complete, a slurry was formed. Water (270 kg) was then added, and the stirring speed was maintained. At this point, the material filling coefficient in the reactor was approximately 0.875. The reactor was heated to 200–210 °C and maintained for 40 hours before being cooled to room temperature. The mixture was filtered. The product had no black spots and was white in appearance. The crude product was washed three times with purified water (150 kg). The washed crude product was transferred to another container, and purified water (300 kg) was added. The pH was adjusted to 4.75–5.25 with hydrochloric acid (partial protonation, i.e., replacing some Na ions with H ions). The mixture was filtered, and then washed twice more with purified water, 150 kg each time. After filtration, the material was dried under reduced pressure in a 100 °C oven to constant weight, yielding 110 kg. The measured potassium ion exchange capacity, KEC, was 3.6 mEq / g. (See also...) Figure 4 It contains no particles smaller than 3 μm. After structural refinement using the Rietveld full-spectrum fitting method, the purity of ZS-9 in the product was 99%. Elemental impurity analysis showed that the content of each element in the product was either undetectable or below the limit value (see Table 1). Wavelength dispersive X-ray fluorescence spectrometry (WD-XRF) determined the silicon content to be 21%, zirconium content to be 22%, and sodium content to be 8%.
[0085] Example 3
[0086] The C276 reactor shown in Example 1 was used, with a volume of 2000L, and the ratio of impeller length to reactor inner radius was adjusted to 0.6:1.
[0087] Sodium hydroxide (180 kg) and water (560 kg) were mixed and cooled to room temperature. Colloidal silica (480 kg) was added, and the mixture was stirred at 80 rpm. While maintaining this stirring speed, zirconium acetate (340 kg) was added. After the addition was complete, a slurry was formed. Water (540 kg) was then added, and the stirring speed was maintained. At this point, the material filling coefficient in the reactor was 0.875. The reactor was heated to 200–210 °C and maintained for 40 hours. Then, it was cooled to room temperature and filtered. The product had no black spots and was white in appearance. The crude product was washed three times with purified water (300 kg). The washed crude product was transferred to another container, and purified water (600 kg) was added. The pH was adjusted to 4.75–5.25 (partial protonation) with hydrochloric acid. The mixture was filtered and washed twice more with purified water, 300 kg each time. After filtration, the material was dried under reduced pressure in a 100 °C oven to constant weight, yielding 250 kg. The potassium ion exchange rate (KEC) was measured to be 3.6 mEq / g, and the volume ratio of particles smaller than 3 μm was 0.83%. Elemental impurity content analysis of the sample showed that the content of each element in the product was either undetectable or below the limit value (see Table 1).
[0088] Comparative Example 1
[0089] The C276 Hastelloy reactor shown in Example 1 was used, with a volume of 1000L, and the ratio of impeller length to reactor inner radius was adjusted to 0.4:1. The reactor sealing device was a magnetic seal.
[0090] Sodium hydroxide (90 kg) and water (280 kg) were mixed and cooled to room temperature. Colloidal silica (240 kg) was added, and the mixture was stirred at 120 rpm. Zirconium acetate (170 kg) was added while maintaining this stirring speed. After the addition, a slurry was formed. Water (270 kg) was then added, and the stirring speed was maintained. At this point, the material filling coefficient in the reactor was 0.875. The reactor was heated to 200–210 °C and maintained for 40 hours before being cooled to room temperature. After filtration, black spots were found in the product. The crude product was washed three times with purified water (150 kg). The washed crude product was transferred to another container, and purified water (300 kg) was added. The pH was adjusted to 4.75–5.25 (partial protonation) with hydrochloric acid. After filtration, the product was washed twice more with purified water, 150 kg each time. After filtration, the material was dried under reduced pressure in a 100 °C oven to constant weight, yielding 108 kg. The final product still contained black spots.
[0091] Comparative Example 2
[0092] The reactor, constructed using the structure shown in Example 1, is made of 316L stainless steel with a volume of 1000L. The ratio of impeller length to reactor inner radius is adjusted to 0.4:1. The reactor is sealed using a magnetic seal.
[0093] Sodium hydroxide (90 kg) and water (280 kg) were mixed and cooled to room temperature. Colloidal silica (240 kg) was added, and the mixture was stirred at 120 rpm. Zirconium acetate (170 kg) was added while maintaining this stirring speed. After the addition, a slurry was formed. Water (270 kg) was then added, and the stirring speed was maintained. At this point, the material filling coefficient in the reactor was 0.875. The reactor was heated to 200–210 °C and maintained for 40 hours before being cooled to room temperature. After filtration, black spots were found in the product. The crude product was washed three times with purified water (150 kg). The washed crude product was transferred to another container, and purified water (300 kg) was added. The pH was adjusted to 4.75–5.25 (partial protonation) with hydrochloric acid. After filtration, the product was washed twice more with purified water, 150 kg each time. After filtration, the material was dried under reduced pressure in a 100 °C oven to constant weight, yielding 112 kg. The final product still contained black spots.
[0094] Table 1 Results of elemental impurities in each batch
[0095]
[0096]
[0097] The above description is merely an illustration of the embodiments of this application and the technical principles employed. Those skilled in the art should understand that the scope of protection involved in this application is not limited to technical solutions formed by specific combinations of the above-described technical features, but should also cover other technical solutions formed by arbitrary combinations of the above-described technical features or their equivalents without departing from the described technical concept. For example, technical solutions formed by substituting the above-described features with (but not limited to) technical features with similar functions disclosed in this application.
Claims
1. A sodium zirconium cyclosilicate raw material, wherein the sodium zirconium cyclosilicate has the molecular formula Na. ~1.5 H ~0.5 ZrSi3O9•2-3H2O; the ZS-9 crystal form accounts for more than 95% of the active pharmaceutical ingredient; the active pharmaceutical ingredient is a solid powder, with particles smaller than 3 micrometers not exceeding 1% of the total volume; the active pharmaceutical ingredient contains 20%~23% silicon, 21%~24% zirconium, 7%~9% sodium, <0.1ppm lead, ≤2.0ppm nickel, and ≤0.3ppm molybdenum.
2. The sodium zirconium cyclosilicate raw material according to claim 1, characterized in that, The elemental content must meet the following requirements: cobalt content ≤ 1.0 ppm, chromium content ≤ 5.0 ppm, and nickel content ≤ 1.0 ppm.
3. A pharmaceutical composition comprising sodium zirconium cyclosilicate raw material as described in any one of claims 1-2.
Citation Information
Patent Citations
Microporous zirconium silicate for the treatment of hyperkalemia
CN103534209A
Microporous zirconium silicate for the treatment of hyperkalemia
CN104797263B
Expanding the use of zirconium silicate compositions and their application methods
CN108137620B
Zirconium silicate and zirconium germanate molecular sieves and process using the same
US5891417A
Microporous zirconium silicate for the treatment of hyperkalemia
CN106170283A